Pilot Study of Telehealth Delivered Rehabilitative Exercise for Youth With Concussion: The Mobile Subthreshold Exercise Program (MSTEP) - Chrisman, Sara P. D.; Mendoza, Jason A.; Zhou, Chuan; Palermo, Tonya M.; Gogue-Garcia, Tierra; Janz, Kathleen F.; Rivara, Frederick P. (Frontiers in Pediatrics, 2021)
BACKGROUND Concussion is common, and up to 30% of youth develop persistent symptoms. Preliminary data suggests treatment with rehabilitative exercise is beneficial, but most programs require frequent in-person visits, which is challenging for youth in rural areas, and has been made more difficult for all youth during the COVID-19 pandemic. We have adapted an exercise intervention to be delivered via telehealth using Zoom and personal fitness devices, which could ensure access to this type of treatment. OBJECTIVE: The goal of this study was to assess feasibility and acceptability of a telehealth delivered exercise intervention for concussion, the Mobile Subthreshold Exercise Program (MSTEP), and collect pilot data regarding efficacy. MATERIALS AND METHODS: All youth received the 6-week MSTEP intervention which included wearing a Fitbit and setting exercise heartrate and duration goals weekly over Zoom with the research assistant. Youth completed standardized measures of concussive symptoms (Health Behavior Inventory, HBI), fear-avoidance (Fear of Pain Questionnaire, FOPQ) and health-related quality of life (Pediatric Quality of life Assessment, PedsQL), as well as a structured qualitative exit interview. We examined change in measures over time using mixed effects modeling, controlling for age, sex, prior concussion and duration of symptoms. We coded qualitative interviews using Thematic analysis. RESULTS: We recruited 19 subjects, 79% female with average age 14.3 (SD 2.2) and mean duration of symptoms 75.6 days (SD 33.7). Participants wore the Fitbit on 80% of days, and completed 94% of surveys and 96% of Zoom calls. Concussive symptoms (HBI) decreased significantly over the 6 week intervention (-10.6, 95%CI: -16.0 to -5.1) as did fear-avoidance (-21.6, 95%CI: -29.8 to -13.5). PedsQL improved during the same time period (+15.1, 95%CI: 8.6-21.6). Approximately three-quarters (76%) of youth rated their care as “excellent.” Participants appreciated the structure of the guided exercise program and the support of the RA. They also enjoyed being able to track their progress with the Fitbit. CONCLUSION: This study provides evidence for the feasibility and acceptability of a telehealth delivered rehabilitative exercise intervention for youth with concussion. Further research utilizing a randomized controlled trial is needed to assess efficacy.